2015
DOI: 10.15406/aovs.2015.02.00045
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Hypoplasia in Oculocutaneous Albinism and the Role of OCT

Abstract: We describe a case of a 16 year old girl with Oculocutaneous albinism (OCA) who presented to us with photophobia and blurring of vision. She showed typical features of OCA, blonde hair, refractive error, iris transillumination and foveal hypoplasia. Our report highlights the role of macular OCT in diagnosis of foveal hypoplasia which is an essential feature of OCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…14,25,27 Studies using OCT devices have shown that individuals with albinism have anomalous foveal morphology owing to foveal hypoplasia whereby the foveal depression is either missing or shallow and there is continuity of the inner retinal layers across the fovea. [4][5][6]12,14,18,31 To this extent, Meyer et al 5 and Holmström et al 14 reported that OCT images in albinism show a widespread thickening of the macular region with no differentiation of the central fovea from the rest of the retina because the ganglion cell and nerve fibre layers extend across the central fovea without thinning. 4,17 However, other studies have noted that there is significant variability in the fovea of individuals with albinism whereby some individuals have low-grade foveal hypoplasia and some of the features associated with normal foveal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,25,27 Studies using OCT devices have shown that individuals with albinism have anomalous foveal morphology owing to foveal hypoplasia whereby the foveal depression is either missing or shallow and there is continuity of the inner retinal layers across the fovea. [4][5][6]12,14,18,31 To this extent, Meyer et al 5 and Holmström et al 14 reported that OCT images in albinism show a widespread thickening of the macular region with no differentiation of the central fovea from the rest of the retina because the ganglion cell and nerve fibre layers extend across the central fovea without thinning. 4,17 However, other studies have noted that there is significant variability in the fovea of individuals with albinism whereby some individuals have low-grade foveal hypoplasia and some of the features associated with normal foveal development.…”
Section: Discussionmentioning
confidence: 99%
“…3 Ocular characteristics of albinism include fundus hypopigmentation, foveal hypoplasia, nystagmus, iris translucency, high refractive errors, non-progressive reduced vision and chiasmal misrouting. [4][5][6][7] Even though recent data related to the incidence and prevalence of albinism in Africa is lacking, it is recognised as a common condition that affects thousands of people with an estimated prevalence ranging from 1 in 5000-15,000 across Africa. 8,9 Specifically in South Africa, Kromberg et al 9 estimated that approximately 14,000 people of the total population in the country have albinism.…”
Section: Introductionmentioning
confidence: 99%